A ballerina's tale [videorecording (DVD)]. - Copeland, Misty (IFC Films, 2016)
Iconic ballerina Misty Copeland made history when she became the first African-American woman to be named principal dancer of the legendary American Ballet Theater. Get the incredible, behind-the-scenes story of how she overcame outmoded ballet culture stereotypes and near career-ending injuries to become one of the most revered dancers of her generation.